Theoretical framework for analysing green web applications - Scheele, Christian Elling (Politik, 2012)
This paper evaluates the appeal of four Danish green web applications. e purpose of the web application is to incentivise behavioural changes aimed at securing a long term sustainable climate by reducing CO2- emissions. e applications are placed in a theoretical framework. is framework shows the dialectical rela- tionship between hardware, software, practice, and discourse. e empirical basis excludes the hardware level. e web applications constitute the software level. Practice is in this case understood in a neo-institutional perspective. e discursive level is the Danish political consensus regarding the need for action in regard to CO2-emissions. e purpose of the evaluation of the appeal of each web application is to test the following hypothesis: A green web application’s appeal bene ts from employing multiple potentially opposed incentives. After establishing the theoretical framework each web application will be analysed according to a template of pa- rameters. e comparative analysis shows how the individual neo-institutional mechanics operates di erently in each application. Each “institution” plays its own role in regard to applications, however it will be argued that an application could bene t from containing elements from all the institutions – both in regard to their appeal and with respect to their key functionality: incentivising behavioural changes.